FORMULATION AND EVALUATION OF ETODOLAC AND TRIAMCINOLONE ACETONIDE LOADED NANO LIPID CARRIER GELS FOR THE THERAPEUTIC MANAGEMENT OF OSTEOARTHRITIS PAIN THROUGH TOPICAL ADMINISTRATION: A COMPARATIVE STUDY - CHAKRABORTY, SOUVIK; GUPTA, N. VISHAL; JAIN, VIKAS; V., BALAMURALIDHARA (International Journal of Applied Pharmaceutics, 2024)
Objective: The present study aims to prepare carbopol-based hydrogels loaded with Etodolac (EDT), and Triamcinolone Acetonide (TCA) incorporated Nanolipid Carriers (NLCs) (EDTg and TCAg) to compare the efficacy and potency of both drugs for Osteoarthritis (OA) pain management. Methods: EDT-NLCs and TCA-NLCs were prepared with the help of the solvent evaporation method after screening the lipids, and the NLCs were optimized. The optimized NLC formulations EDT-NLC and TCA-NLCs were examined for particle size, PDI, zeta otential, Differential Scanning Calorimetry (DSC), Powder X-ray Diffraction (PXRD), Transmission Electron Mcroscopy (TEM) and in vitro release. The prepared EDTg and TCAg have been evaluated with in vitro drug release, ex-vivo skin permeation, and in vivo pharmacokinetic and pharmacodynamic parameters. Results: DSC and PXRD graphs showed a decrease in melting point and the amorphous form of the optimized NLC formulation. Different evaluation tests revealed that the EDT-NLCs and TCA-NLCshad particle size of 161±0.0021 nm and 167.4±0.0010 nm, PDI of 0.148±0.023 and 0.130±0.01, and zeta potential of-14 mV and-15 mV respectively, indicating their distinct nature. In vitro drug release study, ETDg showed 89.84±1.71 % release, while TCAg released 94.75±1.79 % after 24 h of application. ETDg permeated 86.5±1.68% of EDT-NLCs through the dorsal skin, compared to TCA-NLCs 76.5±1.13 %in an ex vivo skin permeation investigation. A pharmacokinetic study identified 76.3±1.98 % of EDT-NLCs and 63.25±2.003 of TCA-NLCs in drug plasma. Pharmacodynamic characteristics like X-ray analysis, Immuno Histochemistry (IHC), and histopathology indicated that EDTg and TCAg managed OA pain. All evaluation tests carried out in this research showed that formulated hydrogels could manage OA. Conclusion: The results suggested in this research prove EDTg to have a higher potentiality than TCAg for the management of OA pain